The static and modal analysis of concrete tank filled with water (Fracture and Structural Integrity, 2025)
Tanks and reservoirs are structural systems designed for storing various liquids, gravels, granular or other bulk materials. Special attention is usually given to the potable water storage. Regarding the increasing scarcity of clean water and the recent lack of it in some regions worldwide, it is essential that these structures have to be carefully analysed and properly designed. Water tanks are significant architectonic works as well. They are typically constructed from steel or reinforced concrete, and most commonly, they adopt the cylindrical shape. Considering their future utilization and regarding other essential circumstances related to the site of their planned placement, they can be situated on the ground, above the ground, partially buried, or fully underground. Due to the expected static and dynamic effects, both static and modal analysis have to be carried out prior to building them up, even within the designing process.This paper provides the numerical analysis of a cylindrical surface-mounted water reservoir by using the Finite element method in Ansys Workbench. The hydrostatic pressure simulating the water acting to the wall was imposed. The static and modal analysis were carried out for empty and fully filled tank. Mutual comparison of various approaches is provided.
Keywords: Tank; Computational model; Staic analysis; Dynamic analysis; Ansys Acoustic